Technical aspects of dental CBCT: state of the art - Pauwels, R (Dentomaxillofac Radiol, 2015)
As CBCT is widely used in dental and maxillofacial imaging, it is important for users as well as referring practitioners to understand the basic concepts of this imaging modality. This review covers the technical aspects of each part of the CBCT imaging chain. First, an overview is given of the hardware of a CBCT device. The principles of cone beam image acquisition and image reconstruction are described. Optimization of imaging protocols in CBCT is briefly discussed. Finally, basic and advanced visualization methods are illustrated. Certain topics in these review are applicable to all types of radiographic imaging (e.g. the principle and properties of an X-ray tube), others are specific for dental CBCT imaging (e.g. advanced visualization techniques).